An approach design and analysis of resource management software for multihoming in-vehicle of IPv6 network - Adeniji, S. D.; Khatun, Sabira; Mohd Ali, Borhanuddin; Raja Abdullah, Raja Syamsul Azmir (Praise Worthy Prize, 2008)
The resource management of Multihoming in nested mobile network raises new issues in the host mobility of ipv6 network. Multihoming facilitates the possibility of switching over to the network path offering better performance. However the key factor in attaining the benefit of multihoming is to ensure that the handoff switches over from one network interface to the other interface with minimal interruption. The aim of mobility support is to make mobile nodes keep connectivity without modification when roaming. The contribution of this paper is to simulate a policy based routing protocol framework that focuses on session preservation by redundancy and Load balancing by selecting the best available interface or enabling multiple interfaces simultaneously, since their management is critical for mobile communication. To manage these two critical resources, we identify the mobility characteristics and hardware configurations of in vehicle networks. The study then proposed a policy based routing protocol using two adaptive session preservation schemes in multihoming, which is refer to as best-connected MR selections based on location and path based type to support nested network of MIPV6 which was simulated using network simulator (NS2).